P-194 Strengthening and diversifying our hospice Board – Actions and outcomes from our governance review. (19th November 2022) - Heaps, Kate; Russell, Ruth
Abstract : Background/Aims: In 2019 we appointed a new Chair to our board; as part of the appointment process the CEO and new Chair agreed to do a timely review of the membership, skills and structure of the Board and related governance. This aimed to strengthen the governance of the charity, support our strategic direction and empower the senior leadership team (SLT) to deliver our transformation agenda. Methods: Very swiftly after the Chair's appointment the board and SLT held an away day and used the charity governance wheel to review all aspects of board performance, we also presented the outcomes of a board skills/diversity audit. The conference presentation will focus on several aspects of this review, our actions and successful outcomes: We agreed that recruitment of several trustees was needed to fill skills gaps on the board and to improve diversity. Recruitment was extremely successful and we have built on this approach in further recruitment. We worked with Digiboard to build on the governance action plan developed after the away day, this helped focus our efforts to strengthen governance e.g. appointment of trustee leads for specific issues (safeguarding, E, D&I), establishment of a new workforce committee, development of a new scheme of delegation and board assurance framework. Results: The presentation will share our experience as well as showing results in trustee recruitment and improvements in governance in the focused areas of the action plan. We will provide feedback from stakeholders to demonstrate improvements in governance/board business. Conclusions: Work to strengthen our governance is inevitably an ongoing process, however, because of the work, we have significantly improved the diversity of our board, expanded the breadth of skills of trustees and strengthened our systems and processes for governance. All of this has contributed to a hospice which is more confident and robust, taking appropriate risks to improve service provision and organisational resilience.